EFEKTIVITAS PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 (Politeknik Kesehatan Kemenkes Bandung, 2021)
COVID-19 is an infectious disease caused by a newly discovered and fatal type of coronavirus. The Minister of Education issued a Circular on the Implementation of Education in the Emergency Period of COVID-19, so learning activities are conducted online to prevent the spread of COVID-19. This study aims to see an overview of the effectiveness of online learning in students of 3rd D III Department of Dental Nursing Poltekkes Kemenkes Bandung during the COVID-19 pandemic. The benefits of this research can contribute to thinking and provide an overview of the effectiveness of online learning. This type of research is Descriptive research with data collection techniques using questionnaires through Google form. The subject of this study was a student of level 3 D III Department of Dental Nursing Poltekkes Bandung. The finding of the study showed online learning to run effectively (75.7%) with the Google Meet app. The obstacle that is often found is that the internet network is less stable, so students expect a monthly internet quota subsidy to facilitate online learning.